Enhancing the antitumour-specific immunity of a lung DNA vaccine in vivo by fusion expression of MAGE-A3 and soluble PD-1. Issue 5 (3rd September 2017) - Chen, Jinhong; Chen, Lu; Zhang, Haochong; Quan, Yan
ABSTRACT: Although DNA vaccines have shown a good antitumor effect in animal models, they are often not effective in clinical trials. This requires researchers to find an effective way to significantly improve the immunogenicity of vaccines. Here, we developed a new DNA vaccine based on MAGE-A3, which has been suggested as a potential target for lung cancer therapy. We enhanced the potency of this DNA vaccine by overcoming tumour-induced immunosuppressive environment through blockade of the PD-1/PD-L pathway using a soluble PD-1 (sPD1). A series of DNA plasmids encoding MAGE-A3, the extracellular domain of murine PD-1 (sPD1) and their conjugates were constructed and injected into female mice intramuscularly (i.m.) followed by an electric pulse. The humoral and cellular immune responses after immunization were evaluated by enzyme-linked immunosorbent assay (ELISA) and enzyme-linked immunospot assay (ELISPOT), respectively. To evaluate the therapeutic efficacy of the plasmids, a mouse model with a MAGE-A3-expressing tumour was designed. Mice vaccinated with the fusion expression plasmid generated the strongest MAGE-A3-specific immune responses. Furthermore, these vaccinations inhibited the growth of MAGE-A3-expressing tumours and prolonged mouse survival. These findings suggest that the combination of DNA vaccines with PD-1 pathway inhibitors may be a promising approach in clinical trials. This approach may be viable for vaccines targeting cancer, as anti-tumour vaccines have demonstrated clinical benefit but PD-1 pathway inhibitors alone have demonstrated poor efficacy so far.